The Ride-Hailing Entrepreneurship Model for The Low-Income Group: An Expert Perspective - Nur Hazwani Zolkifly; Nurul Fadly Habidin; Shahrel Nizar Baharom; Nur Lailatul Husna Mohammad Yusof (International Business Education Journal, 2024)
This research aims to develop and validate the ride-hailing entrepreneurship model for the poor. Utilizing a qualitative method, a semi-structured interview was conducted in two phases. The first phase is an interview of eight ride-hailing drivers in Malaysia to determine the model’s mechanism. Consequently, experts were recruited to validate the model in the second phase. Data from the first phase were analyzed, and themes comprising incentives, processes, cars, and car ownership and financing were created. Conclusively, the bottom 40 participants in the ride-hailing service require assistance. However, they need to be independent in the long term, given that they are gig economy workers. Next, the ride-hailing entrepreneurship model is discussed and revised from the experts’ perspectives for the sustainability of the industry. Finally, some challenges to the model are also described.